The Making of a Market : Credit, Henequen, and Notaries in Yucatán, 1850-1900 - Levy, Juliette, 1968- (Book collections on Project MUSE., 2012)
"Examines the functioning of credit markets in Mexico, through the agency of notaries, during the Yucatan region's nineteenth-century henequen export boom. Explores the mobilization of capital and the creation of credit markets before banks existed"--Provided by publisher.